Some studies on cowpea aphidborne mosaic and pea seedborne mosaic potyviruses in Nepal - Dahal, G.; Albrechtsen, S.E. (Informa UK Limited, 1996)
Various virus‐like symptoms were recorded on field‐grown cowpea(Vigna unguiculataL. Walp) and pea(Pisum sativumL.) during 1989–1990 at the experimental farm of the Institute of Agriculture and Animal Sciences (IAAS), Rampur, Chitwan valley, in the central terai plains of Nepal. The causal agent(s) causing narrow and/or curled leaves, and stunting of pea, and prominent mosaic and vein banding of cowpea were transmitted by both aphids and sap inoculations. Electron microscopic examination of leaf extracts from affected cowpea and pea plants revealed the presence of flexuous filamentous virus particles c. 700 nm long, similar to those of potyviruses. The virions in the leaf extracts from cowpea samples reacted strongly to antibodies against cowpea aphid‐borne mosaic potyvirus (CABMV) in immunosorbent electron microscopy, while the extract from the pea samples reacted strongly to antibodies against pea seed‐borne mosaic potyvirus (PSbMV) in enzyme‐linked immunosorbent assay (ELISA). Time of planting had a significant effect on pea disease incidence and grain yield. The incidence was higher in the late planted pea crop (January) than those planted in November and December. The grain yield and its components (pod filling, number of seeds per pod, and seed weight) were significantly less in the late‐planted crops.